Interior micro‐CT with an offset detector. Issue 6 (28th May 2014) - Sharma, Kriti Sen; Gong, Hao; Ghasemalizadeh, Omid; Yu, Hengyong; Wang, Ge; Cao, Guohua
Abstract : Purpose: The size of field‐of‐view (FOV) of a microcomputed tomography (CT) system can be increased by offsetting the detector. The increased FOV is beneficial in many applications. All prior investigations, however, have been focused to the case in which the increased FOV after offset‐detector acquisition can cover the transaxial extent of an object fully. Here, the authors studied a new problem where the FOV of a micro‐CT system, although increased after offset‐detector acquisition, still covers an interior region‐of‐interest (ROI) within the object. Methods: An interior‐ROI‐oriented micro‐CT scan with an offset detector poses a difficult reconstruction problem, which is caused by both detector offset and projection truncation. Using the projection completion techniques, the authors first extended three previous reconstruction methods from offset‐detector micro‐CT to offset‐detector interior micro‐CT. The authors then proposed a novel method which combines two of the extended methods using a frequency split technique. The authors tested the four methods with phantom simulations at 9.4%, 18.8%, 28.2%, and 37.6% detector offset. The authors also applied these methods to physical phantom datasets acquired at the same amounts of detector offset from a customized micro‐CT system. Results: When the detector offset was small, all reconstruction methods showed good image quality. At large detector offset, the three extended methods gave either visible shading artifacts or high deviation of pixel value, while the authors' proposed method demonstrated no visible artifacts and minimal deviation of pixel value in both the numerical simulations and physical experiments. Conclusions: For an interior micro‐CT with an offset detector, the three extended reconstruction methods can perform well at a small detector offset but show strong artifacts at a large detector offset. When the detector offset is large, the authors' proposed reconstruction method can outperform the three extended reconstruction methods by suppressing artifacts and maintaining pixel values.